JENIS - JENIS IKAN SELAIS (Pisces: Siluridae) DI SUNGAI KUMU KABUPATEN ROKAN HULU PROVINSI RIAU - Sari, Devi Nurusdianita; Purnama, Arief Anthonius; Ade, Filza Yulina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
This study about species of selais fish (Pisces: Siluridae) in Kumu river Rokan Hulu Regency Riau Province which has been carried out from July to September 2014. The study was conducted by survey method mean while samples were collected by stratified sampling method. Samples were caught later identified and analyzed by describing the fish until species that were obtained from catching by usinggill nets, fish netand fishing with three repetitions on the upperstream, middlestream and downstream. Results showed 114 individual of selais fish were found with five species, namely Ompok eugeneiatus, O. hypophthalmus, Kryptopterus schilbeides, K.mononema, K.limpok